Worker Participation and the Politics of Reform - Sirianni, Carmen (Temple University Press, 1987)
This collection examines not only the enormous diversity of imeanings and forms of worker participation in the contemporary period but also its global character. The chapters cover Western and Eastern Europe, the United States and Japan, China, and the Third World. Each of them is informed in some way by the conviction that worker participation is an eminently political phenomenon- that it is about politics and power at the level of the workplace, and that the larger context of social, political, and economic power and organization shapes what happens to participation locally. In this sense, the volume is not simply about internal workplace reforms. Nor is it a country-by-country survey of laws and institutions, but rather a collection of substantive analyses of the actual dynamics of participation and change.